Mechanical properties of hybrid sugar palm/ramie fibre reinforced epoxy composites - Siregar, J. P.; M. R. M., Rejab; Jamiluddin, Jaafar; Zalinawati, Muhamad; Cionita, Tezara; Mawarnie, Ismail; M.H.M., Hamdan (Elsevier Ltd, 2020)
There has been a dramatic increase in natural fibre composites over the past century when natural fibre has performed well as polymer reinforcement. The present study was conducted on the mechanical properties of reinforced epoxy hybrid composites on sugar palm fibre (SPF) (long fibre)/ramie fibre (woven). The hybridizing effect of sugar palm (S) and ramie (R) fibres at different weight ratios was studied at S: R = 15:10 and R:S = 15:10, and thus maintaining the total fibre load by 25% in weight. The composite hybrid specimen consisted of five layers of fibre was prepared alternately. The mechanical properties of composites were analysed by tensile and flexural tests, respectively. The result showed that the tensile and flexural strength of five layer ramie composite was greater than the five-layer SPF composite. On the RSRSR hybrid composite with higher tensile (52.66 MPa) and flexural (80.70 MPa) strength properties among the five-layer SPF and SRSRS hybrid composites, positive hybridisation effects were observed. Since studies on hybrid composite reinforced long fibre SPF were combined with ramie woven reinforced epoxy to improve mechanical performance, the aim to achieve a green composite has become successful.